The leniency of personal bankruptcy regulations in the EU countries - György Walter; Jens Valdemar Krenchel (Risks, 2021)
Discussions on personal bankruptcy regulations are usually focused on the controversial effects of leniency on society, economy, financial markets, entrepreneurship, and labour supply. However, the methodology of measuring leniency has been limited to one-time legislative changes or some elements of the US personal bankruptcy system. In contrast, we create a composite index of personal bankruptcy legislations. We calculate the composite index for 25 EU countries and the US as a benchmark, validate the results, and rank the countries according to the leniency of their personal bankruptcy systems. We analyse the index scores by region, law origin, and the age of the regime. We conclude that the systems show high heterogeneity and cannot be clustered by region or legal origin assumed based on former studies. However, there is a strong association between leniency and the age of legislation. Results indicate that personal bankruptcy policies in the EU are usually launched as creditor-friendly and are later shifted to a more lenient direction.
Keywords: K35; G28; J18; O52; 330; EU; fresh start; leniency; personal bankruptcy; public policy